Mobile applications useful in tinnitus sound therapy – review of tools available in the Polish language - Justyna Kutyba; Wiesław Wiktor Jędrzejczak; Elżbieta Gos; Danuta Raj-Koziak; Piotr Henryk Skarzynski (Medycyna Ogólna i Nauki o Zdrowiu, 2021)
Introduction and objective With the development of tech-nology, the number of users of various mobile applications is growing, including those related to health. They are used by people with multiple health problems, including patients with tinnitus. Currently, there are several hundred tools available on the mobile application market for this group of patients, but most are in English. This review aims to identify mobile appli-cations in Polish that can be useful in tinnitus sound therapy.